2021
DOI: 10.1021/acsphotonics.1c00082
|View full text |Cite
|
Sign up to set email alerts
|

Laser Emission of Thioflavin T Uncovers Protein Aggregation in Amyloid Nucleation Phase

Abstract: There is currently no definitive test for early detection of neurodegeneration which is linked with protein aggregation. Finding methods capable of detecting intermediate states of protein aggregates, named oligomers, is critical for the early stage diagnosis of over 30 neurodegenerative diseases including Alzheimer’s or Parkinson’s. Currently, fluorescence-based imaging using Thioflavin T (ThT) dye is the gold standard for detecting protein aggregation. It is used to detect aggregation in vitro and in various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 69 publications
0
12
0
1
Order By: Relevance
“…Последнее нивелирует потенциальную полезность замедления амилоидной трансформации под действием гликирования. Согласно данным литературы [54,55], ThT может не выявлять образования олигомерных форм амилоида, в отличие от иных форм (мономеры, фибриллы). Можно выдвинуть предположение о том, что сравнительно меньшая интенсивность флуоресценции ThT в пробах, гликированных в присутствии всех ионов d-металлов за исключением меди (II), соотносится с возможностью замедления реакции на стадии образования олигомеров, что, однако, будет являться предметом дальнейших исследований.…”
Section: исследование агрегации и амилоидной трансформации белковunclassified
“…Последнее нивелирует потенциальную полезность замедления амилоидной трансформации под действием гликирования. Согласно данным литературы [54,55], ThT может не выявлять образования олигомерных форм амилоида, в отличие от иных форм (мономеры, фибриллы). Можно выдвинуть предположение о том, что сравнительно меньшая интенсивность флуоресценции ThT в пробах, гликированных в присутствии всех ионов d-металлов за исключением меди (II), соотносится с возможностью замедления реакции на стадии образования олигомеров, что, однако, будет являться предметом дальнейших исследований.…”
Section: исследование агрегации и амилоидной трансформации белковunclassified
“…26,27 For instance, Piotr et al demonstrated amplified stimulated emission with ThT oligomers in solidstate thin films, where different conformations would lead to changes in the lasing threshold. 16 Zhang et al developed a whispering gallery mode (WGM) biolaser by incorporating fluorescein sodium salt into silk fibroin microspheres, and the structural change of the silk fibroin is observed extrinsically from changes of lasing wavelength shifts. 28 Although lasing spectra can provide highly distinguishable and notable optical signatures, most studies require spectrometric systems and precise measurements at a single optical cavity level for readout.…”
mentioning
confidence: 99%
“…15 The major challenge of fluorescence-based imaging is its low sensitivity to oligomeric forms of protein aggregates, which is considered to be the turning point in neurodegenerative diseases. 16,17 To circumvent these challenges, optical technologies have been developed to enhance the signals from protein interactions. One of the well-known emergent approaches is to take advantage of active photonic resonators, also known as biological lasers.…”
mentioning
confidence: 99%
See 2 more Smart Citations